Interleukin-5 Potentiates Sulfidopeptide Leukotriene Production by Human Eosinophils - A. J. M. Van Oosterhout; A. Van Der Poel; L. Koenderman; D. Roos; F. P. Nijkamp (Mediators of Inflammation)
Interleukin-5 (IL-5) has been shown to be a selective eosinophil growth and differentiation factor. In the present study, the effect of recombinant human IL-5 on human eosinophil sulfidopeptide leukotriene production was investigated. IL-5 did not affect leukotriene synthesis in unstimulated eosinophils. However, IL-5 potentiated leukotriene synthesis by eosinophils stimulated with serum treated zymosan (STZ) or the calcium ionophore A23187 by 69% and 135%, respectively. The priming effect of IL-5 was dose dependent, with significant stimulation occurring at 1 000 U/ml for STZ and 100-1 000 U/ml for A23187. Pre-incubation with IL-5 did not increase leukotriene synthesis further.